Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Sumber Daya Manusia (Sdm) Sekolah Menegah Atas Negeri 1 (Sman 1) Yogyakarta - Ahmad Badawi Khabir; Abdul Choliq Hidayat; Ifada Rahmayanti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of principal leadership on HR performance at SMAN I Yogyakarta, the effect of work motivation on HR performance at SMAN I Yogyakarta, the influence of principal leadership and work motivation together on HR performance at SMAN I Yogyakarta. The research design used a survey. with a co-relational approach. The sample used is a saturated sample. The analysis was carried out using descriptive percentage, multivariate, and multiple regression. The effect of the independent variables on the dependent variables is based on the Prevalence Ratio (RP) and Confidence Interval (CI) 95%. Measuring tools using questionnaires, notes from interviews, observations, and documentation. The average principal's leadership is 57.80, work motivation is 65.3 on average, HR performance is 105.26. There is a relationship between the principal's leadership and the performance of human resources (HR) at SMAN I Yogyakarta of 2,978. There is a correlation of work motivation on the performance of human resources (HR) at SMAN I Yogyakarta of 8,670. There is a simultaneous correlation between the principal's leadership and motivation with the performance of human resources at SMAN I Yogya-karta of 79,219. Principal's leadership has a positive and significant impact on the performance of human resources, both educators and education staff at SMAN 1 Yogykarta. Work Motivation Has Positive And Significant Influence On The Performance Of Human Resources Both Educators And Education Personnel At SMAN 1 Yogyakarta. Principal Leadership And Work Motivation Together (SIMULTAN) Have Positive And Significant Influence On The Performance Of Human Resources Both Educators And Education Personnel At SMAN 1 Yogyakarta.